2011
DOI: 10.2309/java.16-1-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of Midline Catheters in the Adult Acute Care Setting – Clinical Implications and Recommendations for Practice

Abstract: Aim and objectives: The aim of this paper was to review published manuscripts on the use of midline catheters, the implications of study findings and recommendations for clinical practice in the acute care setting. Design: Modified integrative literature review Methods: Using key MeSH terms, we searched the electronic databases: CINAHL, Medline, and Embase. The Cochrane and Joanna Briggs databases, Google Search Engine and the reference lists of published materials were also searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 22 publications
(107 reference statements)
0
27
0
Order By: Relevance
“… 3 In adults, EPIV catheter has been showed to reduce cannulation attempts and improve patient satisfaction and hospital efficiency; however, it is associated with complications such as phlebitis and thrombosis. 18 , 19 Neonatal EPIV catheter was first introduced in 1992 20 ; its design has been evolving and improving since then. The latest generation of neonatal EPIV catheter is a short single lumen silicon catheter, manufactured as either a 6 cm or an 8 cm length for neonates (length used on the basis of neonate's size or unit preference), which is designed to remain intravenously for up to 29 days.…”
Section: Background/significancementioning
confidence: 99%
“… 3 In adults, EPIV catheter has been showed to reduce cannulation attempts and improve patient satisfaction and hospital efficiency; however, it is associated with complications such as phlebitis and thrombosis. 18 , 19 Neonatal EPIV catheter was first introduced in 1992 20 ; its design has been evolving and improving since then. The latest generation of neonatal EPIV catheter is a short single lumen silicon catheter, manufactured as either a 6 cm or an 8 cm length for neonates (length used on the basis of neonate's size or unit preference), which is designed to remain intravenously for up to 29 days.…”
Section: Background/significancementioning
confidence: 99%
“…6 An older manuscript by Ryder references the original work conducted in animal labs in the 1970s and 1980s supporting a theory on the effects of osmolality and pH on the venous endothelium. In a 2011 review, Alexandrou and colleagues also reported that they found only a few outcome-based studies showing the effectiveness of midline catheters and that most of these were descriptive and quasi-experimental.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…8,14,15,17,18 Compared with SPCs, MCs are typically more cost-efficient in patients who meet criteria for placement. 5 According to the NANN PICC guidelines, the cost of an MC is equivalent to that of an SPC after 3 to 4 days of therapy.…”
Section: Costmentioning
confidence: 99%
“…13 MC placement does not require radiologic confirmation because the tip lies in a large, peripheral vessel. 6,8,9 INS' 1997 position paper on midline and midclavicular catheters recommended X-ray confirmation only in the following clinical situations: difficulty with catheter advancement; pain or discomfort after catheter advancement; inability to obtain free flowing blood return; inability to flush the catheter easily; the guidewire is difficult to remove or is bent after removal; pain, discomfort, feelings of fullness or coldness; or hearing gurgling sounds during flushing. 2 (p177)…”
Section: Placementmentioning
confidence: 99%